Žanr v tehnološkem remediiranju kulture - Beguš, Ana (Primerjalna književnost, 2019)
This paper relates the concepts of genre, technology and remediation. The substantial nature of technology as an extension and a cultural interface creates new cultural environments. In this process, it transforms the existing genres and generates new ones. The technological environment of the text can thus be understood as a particular level between the textual and the social context which can be materially analyzed. Traditional discourse analysis is mainly concerned with the analysis of ideological narratives in the content but neglects the analysis of the technological interface as an epistemological frame the user is unaware of because it is naturalized (default) in the given cultural context. An outline of today's technological ecosystem is presented with an emphasis on vaporwave as an exemplary genre of new media culture and its relation to traditional (printed) cultural forms.
Keywords: digitalna kultura; elektronski mediji; književnost in tehnologija; medijska ekologija; remediacija; tehnološko okolje; virtualna realnost; žanr